2016
DOI: 10.2507/ijsimm15(2)co10
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Simulation of a Mining Machine Excavating Seabed Massive Sulfide Deposits

Abstract: In this research, the mechanical characteristic parameters of the seabed massive sulfide (SMS) are obtained quantitatively using laboratory uniaxial compression strength (UCS) test and triaxial compression strength (TCS) test. A three-dimensional discrete element (DEM) model of the SMS is developed in the EDEM simulation environment and are then validated by numerically simulating the laboratory UCS and indirect tensile strength (Brazilian disc) tests. A new counter-rotating pick-type drum cutter for excavatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…e three-dimensional discrete element method (3D DEM) was employed to study varieties of cutting force processes. It demonstrated that numerical results have a strong relevance with theoretical and experimental results [24,25]. However, crack propagation and chip separation were not obviously.…”
Section: Introductionmentioning
confidence: 85%
“…e three-dimensional discrete element method (3D DEM) was employed to study varieties of cutting force processes. It demonstrated that numerical results have a strong relevance with theoretical and experimental results [24,25]. However, crack propagation and chip separation were not obviously.…”
Section: Introductionmentioning
confidence: 85%
“…Table I lists the basic parameters of the gear pair, where the import power P is 10 kW, the driving gear rotate speed n 1 is 960 r/min, and the load factor K a is 1.526. 4 When the finite element model of the gear pair is established and transient analysis is performed, the stress distribution of the carburized gear pair in any position can be obtained at any moment [26,27]. The time-history (time-hist) curve of the maximum stress can be obtained by reading the maximum contact stress on the surface and the maximum equivalent stress on the tooth root of the carburized gear.…”
Section: Simulation Analysis and Discussionmentioning
confidence: 99%
“…The numerical simulation method is used to simulate the bolt-shotcrete support structure of tunnel, and the maximum vertical displacement of the tunnel vault is calculated [14,15]. FLAC is the abbreviation of Fast Lagrangian Analysis of Continua, originated from fluid dynamics, and first applied in the field of solid mechanics by Willkins.…”
Section: Robustness Indexmentioning
confidence: 99%